Daya Tarik Wisata di Sari Ater Hotel & Resort - Muhammad Noegi; Muhammad Fadhil Suyarto (Pusat Riset dan Inovasi Nasional, 2023)
The increasing development of Ciater hot spring tourism in Subang Regency has encouraged the management to build resort hotel facilities. The design of this project refers to ecotourism principles. The design area is 47,000 m 2 consisting of 23 villa units, supporting facilities and recreational facilities. This project was designed by raising three main issues, namely environmental issues, privacy, and atmosphere. These three issues are then elaborated into the main concept, namely Tranquil Coexistence of Nature and Architecture which means harmony between architecture and its environment. The beautiful scenery of the mountains of West Java and the sloping contours of the land are a reference for laying out the mass composition and zoning on the site. The arrangement of masses in the eco-resort area is made natural by avoiding angles and symmetrical geometries. The concept of an open mass and roof form adapted from Sundanese architecture is a reference for spatial planning and building masses in villa facilities and public facilities using local materials. As an effort to reduce degradation of environmental quality in Ciater, the design of the site utility was made using a water sensitive landscape design approach in which the water element will be recycled and reused on the site. The results of this eco-resort design are expected to be able to contribute to environmental preservation, increase the tourism potential of Ciater hot springs, and increase the welfare of the surrounding community in line with the increasing number of visitors who come.